Comparative Evaluation of Sulfuric and Hydrochloric Acid Atmospheric Leaching for the Treatment of Greek Low Grade Nickel Laterites - Christiana Mystrioti (The Minerals, Metals and Materials Society)
Greece is the only EU country with extensive nickel laterite deposits. Since the 1960s, the Greek laterites are treated for ferronickel production via a pyrometallurgical route, which involves pre-reduction of the ore in rotary kilns and reduction smelting in electric arc furnaces. Due to the rising cost of energy and the decreasing grade of mined laterites, the pyrometallurgical treatment is economically marginal. For this reason, alternative treatment processes are currently under investigation. Potential applicability of hydrometallurgical treatment, using either H2SO4 or HCl, under atmospheric pressure conditions, for Ni and Co extraction from two low grade laterite ores, was examined in the present work. The two samples were selected to represent the different mineralogical composition of the saprolitic and limonitic ore deposits of the Greek laterites. The investigated parameters were temperature (65–90 °C), acid concentration (1–4 N) and solid to liquid ratio (10–30% w/v). The results indicated that HCl was more efficient than H2SO4 for the treatment of the saprolitic ore; Ni and Co extractions were very high for both elements, up to 98% and 96% respectively, while H2SO4 could leach efficiently Ni, up to 100%, but extracted only 34% of Co. Hydrochloric acid was also more efficient for the treatment of the limonitic ore, with Ni and Co extractions up to 98.3% and 87.6% respectively. With H2SO4 the maximum extractions were 71.3% for Ni and 52.1% for Co.